Effect of Glutaraldehyde on Cell Viability, Triphenyltetrazolium Reduction, Oxygen Uptake, and β-Galactosidase Activity in Escherichia coli - Munton, T. J. (1973)
Acid (pH 5) and alkaline (pH 8.5) glutaraldehyde solutions were compared for their effects on cell viability, oxygen uptake, and β-galactosidase activities in Escherichia coli. The action of glutaraldehyde at pH 7 on dehydrogenase activity was also studied. Dehydrogenase activity was inhibited at aldehyde concentrations which had little effect on cell viability. In contrast, oxygen uptake and β-galactosidase activity took place in cells killed by acid or alkaline glutaraldehyde. The effect of glutaraldehyde on dehydrogenase activity and β-galactosidase activity of disrupted suspensions was also investigated. The dialdehyde was considerably less inhibitory to these enzyme systems than to those of whole cells, and it is thus feasible that the results with whole cells are a consequence of its interaction with, and strengthening of, the outer cell surface, thereby preventing ready access of substrate to enzyme.